1986
DOI: 10.1136/jcp.39.11.1193
|View full text |Cite
|
Sign up to set email alerts
|

Idiopathic membranous glomerulonephritis: aspects of geographical differences.

Abstract: SUMMARY Clinicopathological studies of 89 cases of idiopathic membranous glomerulonephritis was carried out to investigate the clinical and histopathological characteristics of the disease. The results were compared with those of previous published reports to observe whether any difference between Japanese and caucasian patients exists. There were no obvious differences as to main clinical features, although an apparently better prognosis in our data was observed during long term follow up. In renal biopsy fin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
18
0
1

Year Published

1990
1990
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(25 citation statements)
references
References 13 publications
6
18
0
1
Order By: Relevance
“…The cause of improved outcomes in our study is unclear and might have resulted from the frequent use of RAAS blockades (75.9%) and immunosuppressive therapies (81.9%). Otherwise, it may support the theory that the clinical course in Asian patients is benign as compared to that in the Caucasian population [1921]. Through analyses of patients presenting with NS, we showed that maintenance of remission state is important for the preservation of long-term renal function.…”
Section: Discussionsupporting
confidence: 61%
“…The cause of improved outcomes in our study is unclear and might have resulted from the frequent use of RAAS blockades (75.9%) and immunosuppressive therapies (81.9%). Otherwise, it may support the theory that the clinical course in Asian patients is benign as compared to that in the Caucasian population [1921]. Through analyses of patients presenting with NS, we showed that maintenance of remission state is important for the preservation of long-term renal function.…”
Section: Discussionsupporting
confidence: 61%
“…First, diagnostic criteria of idiopathic MN differ from ours to Zeng et al's, which excluded all the cases with glomerular complement 4 (C4) and/or C1q deposition, even with no identified secondary cause. Incidence of idiopathic MN in our study approaches other studies by Abe et al (1986) (Japan), Cahen et al (1989) (France), Honkanen (1986) (Finland), and Gluck et al (1973) (United States), with 65%, 79.3%, 69.8%, 62.3%, respectively. Second, patients with tongue coating score more than 7 and less than 11 were excluded in our study, which might be a reason for the greater incidence of idiopathic MN.…”
Section: Discussionsupporting
confidence: 85%
“…35 Furthermore, this or other sulfhydryl groups on the extracytoplasmic domains within this molecule could be modified owing to environmental, accidental, or therapyrelated exposure to heavy metals (e.g., gold or mercury), a known cause of secondary membranous nephropathy. [36][37][38][39] We speculate that sequence variants within HLA-DQA1 alleles that are unique to idiopathic membranous nephropathy lead to the presentation of such peptides to immunocompetent cells, resulting in autoantibody formation. Thus, the coexistence of risk alleles in HLA and PLA2R1 in the same person may circumvent the tightly regulated adaptive immune system and allow for the development of idiopathic membranous nephropathy.…”
Section: Discussionmentioning
confidence: 99%